Towards the development of mobile augmented reality model - Fatin Norsyafawati Mohd Sabri; Nik Zulkarnaen Khidzir; Ahmad Rasdan Ismail (Universiti Malaysia Kelantan, 2015)
Augmented reality (AR) is a variation of virtual reality (VR). Many manufacturing companies and computer science have been studying the AR technology as a new human machine interface with the development of VR technologies. However, most of software and methods for digital manufacturing require the perfect 3D models of the whole product or the whole system in virtual reality to represent the target system and surrounding environment. Certain manufacturing companies which realize the weaknesses of VR based digital manufacturing technologies have been studying AR technology as new interface between man and machine. Therefore, this study would become the basic idea for the researchers to explore and increase the experience of the user, who can retrieve this information by a user-friendly interface.